O1-S05.03 Behavioural factors associated with Bacterial vaginosis (BV) in women who have sex with women (WSW): the Women On Women's (WOW) Health Study. (10th July 2011) - Bradshaw, C; Bilardi, J; Walker, S; Vodstrcil, L; Garland, S; Hocking, J; Chen, M; Peterson, S; Fehler, G; Fairley, C
Abstract : Background: We are conducting a national 2 year cohort study in 400 Australian WSW to determine the behavioural and microbiological factors associated with prevalent and incident BV in women and their sexual partners. Data from the cross-sectional study will be presented. Methods: WSW were recruited using internet, festival and media-based promotion and were ineligible if they are postmenopausal, pregnant or had not had a female sex partner (FSP) in the last 18 months. Study-kits containing consent forms, questionnaires, swabs and slides were sent to participants and returned by post. At baseline, women self-collected three consecutive vaginal swabs and slides at weekly intervals and completed detailed demographic behavioural data via an online or paper-based questionnaire. Gram-stained self-collected vaginal smears (SCVS) were scored by the Nugent method. Women were classified as having prevalent BV if ≥1 slides had a Nugent score (NS) of 7–10, intermediate flora if ≥1 slides had a NS=4–6 and normal flora if all three slides had a NS=0–3. Univariate and multivariate analyses were performed using SPSS to examine the association between BV and behavioural practices. Results: In February 2011, 342 (86%) women had been recruited and 314 (92%) women had completed all cross-sectional requirements. Median age was 31 years (range 19–49), 309 (98%) reported a FSP in the last year, 253 (81%) had a current sexual partner (95% female) and 246 (78%) reported vaginal sex with a male in the past. The prevalence of BV was 29% (95% CI 20% to 38%) in women providing ≥1 SCVS. Two hundred and seventy-five (88%) women provided all three SCVS of which 178 (65%) had stable normal flora on all slides, 56 (20%) stable BV and 41 (15%) had unstable flora transitioning between ≥1 Nugent categories over the three slides. Multivariate analysis found that being a current smoker of cigarettes or marijuana (Adjusted OR AOR =2.2; 95% CI: 1.3% to 3.8%) and having >5 lifetime FSPs (AOR =1.8; 1.0 to 3.01) was significantly associated with prevalent BV. A borderline association with FSP receptive oral sex (AOR=3.2; 0.9 to 11.0) was evident. BV was not associated with increased age or numbers of male partners. Conclusion: Prevalent BV is common (30%) in WSW and is strongly associated with smoking and increasing numbers of FSPs but not male partners. A high proportion of WSW had stable vaginal flora (85%) over a 3 week period. This study aims to advance our understanding of epidemiology of BV in WSW.